Pengaruh Pendapatan Bunga Terhadap Profitabilitas Pada Perusahaan Perbankan Yang Terdaftar Di BEI Periode 2017-2018 - Nurfitrani Harnaen, Yulia (Nusa Putra University, 2021)
Profitability is the analysis of financial ratios that is carried out by an entity to identify an entity as long as it has a profit and to assess the extent to which the entity is generating its profits. The research aims to prove that interest income has an effect on profitability. The population during the study were banking companies on the IDX for the 2017-2018 period totaling 42 companies, and the sample was taken using purposive sampling obtained 13 companies. Hypothesis testing uses simple linear regression analysis to see the influence between variables through SPSS. The t-test result shows that the sig <Î± value means that interest income has an effect on profitability (ROE).